In silico pan-cancer analysis reveals prognostic role of the erythroferrone (ERFE) gene in human malignancies - Xu, Qingyu; Altrock, Eva; Schmitt, Nanni; Streuer, Alexander; Rapp, Felicitas; Nowak, Verena; Obländer, Julia; Weimer, Nadine; Palme, Iris; Göl, Melda; Hofmann, Wolf-Karsten; Nowak, Daniel; et al. (International journal of molecular sciences, 2023)
The erythroferrone gene (ERFE), also termed CTRP15, belongs to the C1q tumor necrosis factor-related protein (CTRP) family. Despite multiple reports about the involvement of CTRPs in cancer, the role of ERFE in cancer progression is largely unknown. We previously found that ERFE was upregulated in erythroid progenitors in myelodysplastic syndromes and strongly predicted overall survival. To understand the potential molecular interactions and identify cues for further functional investigation and the prognostic impact of ERFE in other malignancies, we performed a pan-cancer in silico analysis utilizing the Cancer Genome Atlas datasets. Our analysis shows that the ERFE mRNA is significantly overexpressed in 22 tumors and affects the prognosis in 11 cancer types. In certain tumors such as breast cancer and adrenocortical carcinoma, ERFE overexpression has been associated with the presence of oncogenic mutations and a higher tumor mutational burden. The expression of ERFE is co-regulated with the factors and pathways involved in cancer progression and metastasis, including activated pathways of the cell cycle, extracellular matrix/tumor microenvironment, G protein-coupled receptor, NOTCH, WNT, and PI3 kinase-AKT. Moreover, ERFE expression influences intratumoral immune cell infiltration. Conclusively, ERFE is aberrantly expressed in pan-cancer and can potentially function as a prognostic biomarker based on its putative functions during tumorigenesis and tumor development.
Gesehen am 14.10.2024